A Simulation Analysis of the Power Characteristics of Some Popular Estimators Under Different Risk and Materiality Levels - Smieliauskas, Wally (Journal of Accounting Research, 1986)
Wally Smieliauskas, A Simulation Analysis of the Power Characteristics of Some Popular Estimators Under Different Risk and Materiality Levels, Journal of Accounting Research, Vol. 24, No. 1 (Spring, 1986), pp. 217-230